Qualità nella ricerca, qualità della ricerca - Leonardo Cannavò (Quaderni di Sociologia, 2008)
The concept of «quality», applied to research evaluation, is being criticised first as it is conceived as absolute, instead of highly specific to public expectancies; secondly, because – contrary to the scientometric approach – quality can be evaluated, and not measured; thirdly, the definition of research quality is theory-laden, or better, context-laden. The article stresses 6 types of context, relevant to shape the concept and evaluation of research quality: 1. the type and level of research finalization; 2. the level of aggregation of social expectancies; 3. the systemic and institutional context of research; 4. the socio-cognitive subsystem (or, in other words, the disciplinary matrix) of research; 5. the specific relevance of research contributions in reference to scientific expectancies; 6. the kind of decision to be taken as a consequence of the evaluation process. The A. concludes rejecting the scientometric approach to research evaluation, inasmuch scientometric indices measure the productivity and/or the diffusion, but not the «quality», of research, while deferential citing, overpublishing, self-citation, and lobbyist citation can alter the functioning of the recognition of excellence system.